Las semánticas de la posteridad: el cine y la matriz de las generaciones futuras - Francescutti, Pablo (Política y Sociedad, 2011)
In the second half of the XXth century, the semantics of posterity underwent a dramatic transformation, expressed in the importance of the notion of future generations. Ushered in by environmental discourse, this construct has gained an outstanding presence in the public realm, as much as it conveys the idea of the moral responsibility for the long term consequences of our actions, a responsibility focused on the welfare of our descendants. This new understanding of the future has inspired a copious literature about its legal and politic implications (i.e. sustainable development and the precautionary principle); although little has been said of the social and cultural circumstances of its genesis. In this study we turn to science fiction cinema to highlight the making of that category. This film genre appears suitable for this research because one of its themes concerns the relationships between contemporary people and future Humanity. Our film analysis allow us to visualize the trajectory of this category since its appearance in the Fifties (with its actual meanings) and to show how it was modulated by the social necessity of an external point of view upon which risk observations can be based.
Keywords: Future Generations; Posterity; Risk; Cinema; Science Fiction; Environmentalism